2020
DOI: 10.1136/bmjopen-2019-036530
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study of antibiotic prescription patterns and associated drivers in Sudan, Guinea-Bissau, Central African Republic and Democratic Republic of Congo

Abstract: ObjectivesThe objective of this study was to address the knowledge gap regarding antibiotic use in Medecins Sans Frontiéres (MSF) projects located in Africa by exploring antibiotic prescription and consumption habits and their drivers at different healthcare levels.DesignThis study used an exploratory study design through thematic analysis of semistructured, in-depth interviews, focus group discussions (FGDs) and field observations in order to understand the main drivers influencing current antibiotics prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Although access to antimicrobials from public facilities is usually given after a clinical assessment and diagnosis as found in our study, this is limited by various health system challenges. Similar to our findings, other studies have also shown that challenges such as stock-out of essential medicines, long distances between community dwellings and health facilities, high cost of transportation to facilities, and long waiting times restrict access to antimicrobials in the public health sector [ 36 , 37 ]. The role of CHWs in dispensing antimicrobials addresses some of these challenges since they work closer to the communities.…”
Section: Discussionsupporting
confidence: 89%
“…Although access to antimicrobials from public facilities is usually given after a clinical assessment and diagnosis as found in our study, this is limited by various health system challenges. Similar to our findings, other studies have also shown that challenges such as stock-out of essential medicines, long distances between community dwellings and health facilities, high cost of transportation to facilities, and long waiting times restrict access to antimicrobials in the public health sector [ 36 , 37 ]. The role of CHWs in dispensing antimicrobials addresses some of these challenges since they work closer to the communities.…”
Section: Discussionsupporting
confidence: 89%
“…In that study, healthcare providers acknowledged consciously prescribing higher-than-recommended amounts of antibiotics due to the scarcity of follow-up visits, which were typically conducted just when patients were in critical condition. This difficulty in adopting a “wait-and-see” approach was attributed to the limited availability of follow-up care [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, factors that influence the prescribing of antibiotics by general practitioners (GPs) include patients' demands for antibiotics, prescribing antibiotics to save time due to the perception that it takes longer to explain why antibiotics are not needed, concerns that the patient may not return for follow up, uncertainty in the diagnosis where antibiotics may be warranted, concerns about possible complications, preservation of the doctor-patient relationship, and knowledge and attitudes to AMR [10,11].…”
Section: Introductionmentioning
confidence: 99%